Analisis Potensi dan Tingkat Pemanfaatan Sumber Daya Ikan di Perairan Balikpapan - Luh Putri Adnyani; Nurmawati Nurmawati; Indira Anggriani (Universitas Gorontalo, 2019)
Balikpapan waters have a high potential for fisheries with an area of 300 km2. However, through BPS data in 2018, Balikpapan only accounts for 5% of East Kalimantan's fisheries production. Therefore, research related to the potential of fisheries in Balikpapan was conducted. The method used was a questionnaire to 40 fishers in the Manggar and Sepinggan villages. Several categories are asked. As for the results of the questionnaire, it is found that the condition of Balikpapan fishers are as follows: The fishing gear used by fishers in Balikpapan varies but is dominated by fishing nets and fishing rods. The length of boat ownership of 40 fishers is 37% of fishers having their boat between 1 to 3 years. Regarding the production, fishers only get 1 kg in worst season but could reach 80 kg in peak season. The number of trips for most Balikpapan fishers n is 30 days a month, but also depends on the weather. The South monsoon, many fishers do not go out to sea. Every trip, fishers have capital of between Rp. 100,000 up to Rp. 500,000. The education level of Balikpapan fishers is mostly elementary and junior high school graduates. Most of Balikpapan fishers are in the productive age range, 30-40 years. Regarding fishing boat ownership, it can be categorized into two types, namely own boats or shared boats. For shared boats, boat owner get a more significant share of the production. The catch of fishers is still not processed. Catches that are not sold are eaten alone or given to neighbours. More than half of the Balikpapan fishers who were questioned did not have any skills other than fishing. The ratio of fishers who have received training from the government, private sector or academics with those who do not is 6: 4. Balikpapan fishers are not familiar with aquaculture.